SEM Investigation of Microlayer Formation and Study of Wear Mechanism in Friction Composites - Yusubov, F.F. (Herald of Azerbaijan Engineering Academy, 2022)
The paper is devoted to the study of wear surfaces of friction composite materials obtained by powder metallurgy. A scanning electron microscope (SEM) equipped with an energy-dispersive X-ray spectrometer (XRD) is used to study changes in contact surfaces under various friction conditions and the nature of the microlayer. The results show that oxidation wear is characteristic of almost all stages. The sequence of formation of frictional microlayers is also determined.